HUBUNGAN ADIPONEKTIN DENGAN GAGAL JANTUNG KONGESTIF - Agung Budiyasa, Dewa Gde; Santoso, Anwar (journal of internal medicine, 2008)
Adipose tissue synthesis several protein involved in the regulation of insulin action and lipid metabolism. Among theprotein adipocytokines, adiponectin is the most abundant and exerts profound anti-diabetic, anti-atherogenic, and anti-inflammatoryroles. Adiponectin may contribute to the regulation of vascular hemostasis by its ability to affect several signaling pathwaysin the vessel wall and modulate excess inflammatory responses. In the heart, adiponectin serve as a regulator of cardiacinjury through modulation of pro-survival reaction, cardiac energy metabolism, and inhibition of hypertropic remodelling. Manyeffect of adiponectin in the cardiovascular system correlate with the activation of both AMPK and Cox-2.Adiponectin levels may influence the development of CHF, but the epidemiological data are somewhat complex. This isdue in part to the fact that while higher body mass indices are a risk factor for heart failure, obesity is a predictor of improveprognosis in patients with establish CHF because wasting is strongly associated with the increased risk of death in the final stageof this disease. In this regard, high adiponectin levels are a predictor of mortality in patients with heart failure. Presumably, thisparadoxical relationship exist because high body mass, hence low protein, favors survival in endstage heart failure. Therefore,further studies should examine adiponectin levels in patients with stable heart failure